International journal of conflict engagement and resolution (Eleven International Publishing, 2013)
"The International Journal of Conflict Engagement and Resolution (IJCER) is produced by the Graduate Program on Conflict Resolution, Management and Negotiation at Bar-Ilan University. It publishes articles from scholars, graduate students and practitioners that address conflicts, defined broadly to include: interpersonal, familial, inter- and intra-organizational/business, national and international conflicts. It endorses all disciplines with the aim to contribute to the empirical, theoretical, prescriptive or practical understanding of conflicts in order to better creatively engage them"--publisher's website.